The uses of Technical Material Sheet (TMS) for the maintenance of a government office building in Putrajaya / Nurul Izzati Shamsul Bahri - Shamsul Bahri, Nurul Izzati (Universiti Teknologi MARA, Perak, 2019)
Building Information Modelling (BIM) has become an essential part of the construction industry due to its modern methods of managing information during key stages if the project. So, it is no surprise to see BIM being integrated into Facility Management (FM) as an effort to enhance progress and work quality. Therefore, this report will discuss the Technical Material Sheet (TMS) which is the process of collecting and reviewing information from different items based on the category of trade. The case study is conducted at a government office building in Precinct 1, Putrajaya the main objective of this report includes the process of producing TMS and challenges faced during the production of TMS. Lastly, this report will also explore the recommendations and solutions that can overcome these problems through observations or literature reviews. In summary, BIM plays a powerful role in the construction field that can leave a massive change to the world.